Rules, punishment, penaltiesand vulnerability to STD-Aids in the everyday lives of female prisoners - Giordani, Annecy T.; Bueno, Sônia M.V.; Kantorski, Luciane P. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Background: In Brazil, closed institutions such as prisons for females, punish prisoners by depriving them of freedom and causing them additionalsuffering which is materialized in the form of physical and psychic violence. In this setting, once they are involved with crime, these women become morevulnerable to STD-aids due to sexual abuse. Objectives: To identify punitive and normative actions in the everyday lives of female prisoners by relatingthem to illegal violent practice which is made natural by the State as a way to discipline agencies. Methods: A qualitative research was conducted by meansof periodical visits. Systematic observation was carried out and later recorded. Structured interviews containing guiding questions were used with (15)female prisoners and the chief police officer/warden of a public prison for females in the interior of São Paulo State. Results: Most women were 18 to 30 years old, single mothers, had low educational level and had been convicted of drug trafficking. The investigated prison more frequently applied isolationas a form of punishment, life protection for prisoners who had been threatened with death or in order to avoid fights among the inmates. Other types ofpunishment were: prohibition of visitors, loss of remission, suspension of mail receipt, transfer to other institutions, including the report of physicalaggression. Conclusions: The Brazilian prison system leads to violence, which hinders the recovery of law breakers and their social re-inclusion. In thischain, as occurs in almost all others, there is no adequate medical care to HIV-infected inmates or for those with aids nor a program of preventive educationagainst STD for females.